Analysis of the Impact of Investor Herding Behavior on Cryptocurrency Investment Decision-Making - Yovita, Felicia Viany (Riviera Publishing, 2025)
This study examines the influence of herding behavior on investment decision-making in the Indonesian cryptocurrency market. Behavioral finance posits that investor decision-making is frequently driven by psychological biases and prevailing market sentiment, leading to herding behavior—where individuals tend to imitate the investment choices of the majority rather than conducting their own independent evaluations. Using a qualitative-method approach, this study is conducted among individual investors who are engaged in cryptocurrency investment in Indonesia. Purposive sampling technique was used for data collection and the sample consisted of 50 questionnaires. Contrary to prior empirical evidence suggesting that herding behavior negatively affects investment decision-making within speculative markets such as cryptocurrency, the results of this study indicate that herding behavior does not exert a statistically significant influence on the investment decisions of Indonesian cryptocurrency investors. The findings suggest that, in the context of the Indonesian market, investors may rely more on personal judgment or alternative decision-making mechanisms rather than being influenced by crowd behavior. This study contributes to the existing body of literature by providing region-specific insights into behavioral finance and herding phenomena, highlighting the importance of contextual and cultural factors in shaping investor behavior within emerging markets.